Impact of short-term high-fat feeding on lipid droplet content in mouse oocytes - Ryutaro AIZAWA; Megumi IBAYASHI; Tomomi HATAKEYAMA; Takayuki TATSUMI; Satoshi TSUKAMOTO (The Society for Reproduction and Development, 2020)
Mature mammalian oocytes contain lipid droplets (LDs), which are neutral lipid storage organelles critically important for energy metabolism. In mice, maternal obesity, induced by long-term (> 3 months) high-fat feeding, contributes to the accumulation of LDs in mature oocytes. However, few studies have investigated the influence of short-term high-fat feeding on LD content. In this study, we demonstrated that 3 weeks of high-fat feeding is sufficient to increase LD content and intracellular triacylglycerol levels. Using a two-step centrifugation technique to release LDs into the perivitelline space, we found that short-term high-fat feeding increased the level of LDs in MII oocytes and that 3 days of high-fat feeding were sufficient to increase efficiency of LD release. Collectively, our study suggests that short-term high fat feeding can have a higher impact on lipid metabolism during oocyte maturation.